Pentingnya Memahami Entrepreneurship Secara Biblikal bagi Hamba Tuhan - Sabaria Zega (Sekolah Tinggi Alkitab Jember, 2019)
The servant of God who serves does not always depend on the life of the church served if the church economic is not established yet. God's servants can work, or empower their congregation to work. This article is a qualitative research literature that aims to show the importance of God's servants' understanding of entrepreneurship in order to be able to apply it to the congregation that they serve. The method used is descriptive and biblical analysis by considering several texts that can be a reference for entrepreneurship in the congregation. In conclusion, several passages like Matthew 25: 14-30, Acts 18: 3, and 2 Thessalonians 3: 6-15 can be used as a foundation for God's servants to teach entrepreneurship to their congregations. AbstrakHamba Tuhan yang melayani tidak selalu menggantungkan kehidupannya dari jemaat yang dilayani jika kehidupan perekonomiannya belum mapan. Hamba Tuhan dapat bekerja, atau memberdayakan jemaatnya untuk bekerja. Artikel ini merupakan sebuah penelitian kualitatif literatur yang bertujuan untuk menunjukkan pentingnya pemahaman hamba Tuhan tentang entrepreneurship agar dapat menerapkannya dalam jemaat yang dilayaninya. Metode yang digunakan adalah deksriptif dan analisis Alkitab dengan mempertimbangkan beberapa nas yang dapat menjadi acuan bagi entrepreneurship dalam jemaat. Kesimpulannya, beberpa nas seperti Matius 25:14-30, Kisah Para Rasul 18:3, dan 2 Tesalonika 3:6-15 dapat dijadikan landasan untuk hamba Tuhan mengajarkan entrepreneurship bagi jemaatnya.